Mind perception of God in Japanese children. (5th March 2018) - Moriguchi, Yusuke; Takahashi, Hideyuki; Nakamata, Tomoko; Todo, Naoya
Abstract : There is a theoretical debate regarding whether children represent God with reference to a human. Most previous studies have assessed this issue focusing on knowledge/omniscience in western children. This study used a theoretical framework characterising mental capacities in terms of motivational/emotional (experience) and cognitive (agency) mental capacities and tested whether Japanese children discriminated between God, a human, a baby and an invisible agent according to these capacities. Three‐ to 6‐year‐old children were asked about the experience and agency of the agents. The results revealed that children discriminated God from a human in terms of mental capacities including experience and agency in 3‐year‐old children. On the other hand, 4‐ to 6‐year‐old children, but not 3‐year‐old children, discriminated a human from a baby and an invisible person. The results suggest that the Japanese children's representations of God differed from their representation of a human during preschool years.